Safety Management in Sea Reclamation Construction: A Case Study of Sanya Airport, China - Jinchao Ma; Wei Zhong; Xiaoliu Zhu (Advances in Civil Engineering)
Urbanization has increased the burden on land resources. Artificial island construction has been proven as an effective method for addressing these land resource problems; however, few studies have been conducted on the safety of sea reclamation construction. This paper proposes a systemic approach to the complete safety management process in sea reclamation engineering, including safety system design, analysis, control, and assessment, using the Sanya Sea Reclamation Airport, Hainan Province, China, as a case study. A total of 145 steel cylinders must be vibrated and sunk into the seafloor to create a 9 km quay wall. Owing to their large size, the steel cylinders have been divided into different segments, and an assembly jig is employed to ensure a safe production process. Considering the hazardous working environment in sea reclamation construction, a numerical analysis is conducted to investigate the safe repertory of these steel cylinders and verify the reliability of the selected scheme for their transportation. Finally, control measures are adopted to ensure a safe vibration and sinking procedure for the steel cylinders. The proposed approach could be used to provide safety management guidelines for artificial island engineering and construction.